2006
DOI: 10.1159/000094708
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Fungal Disease: An Under-Recognized Entity

Abstract: Most fungi enter the human body via inhalation; however, endobronchial fungal infection (EBFI) seems to be a rare manifestation compared to pulmonary or systemic disease. This presentation seems to be related to environmental factors as well as to the host status. With the increasing popularity of flexible bronchoscopy, it is being recognized with a higher frequency. Bronchoscopic findings in EBFI vary from mild mucosal inflammation to central airway obstruction. We searched English literature related to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 199 publications
2
86
2
2
Order By: Relevance
“…Endobronchial obstruction in association with other pulmonary abnormalities, similar to our cases, have been described (14,19), and, unexpectedly, appeared to be more common in immunocompetent patients (19). However, the incidence of direct airway involvement remains unknown (19).…”
Section: Discussionsupporting
confidence: 78%
“…Endobronchial obstruction in association with other pulmonary abnormalities, similar to our cases, have been described (14,19), and, unexpectedly, appeared to be more common in immunocompetent patients (19). However, the incidence of direct airway involvement remains unknown (19).…”
Section: Discussionsupporting
confidence: 78%
“…How organizing pneumonia is generated in patients with Aspergillus infection unknown, but a few studies of semi-invasive pulmonary aspergillosis have found that organizing pneumonia can develop in areas without hyphae (11). As was seen in the present case, A. fumigatus infection is a leading cause of ITBA, followed by A. flavus, A. niger and A. nidulans (12). The fact that the non-segmental consolidations with ground glass opacities rapidly spread from the right basal lung area to the right middle lobe or left whole lung implies that those lesions were probably caused by SLE/DM.…”
Section: Discussionsupporting
confidence: 67%
“…Diabetic individuals have increased serum iron because of impaired transferrin binding, which may contribute to their increased risk of infection. 3 Patients usually present with prolonged high-grade fever that is unresponsive to broad-spectrum antibiotics. Nonproductive cough is a common symptom, whereas hemoptysis, pleuritic chest pain, and dyspnea are less common.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of EBM cases have been described in patients with diabetes mellitus. 3 Furthermore, pulmonary mucormycosis tends to present a more subacute and less fulminant course in these patients. 2 Our patient's initial presentation was similar to an acute bacterial lung infection that partially responded to antibiotic therapy, and he subsequently presented with hemoptysis, a common feature in EBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation